2020
DOI: 10.31729/jnma.5285
|View full text |Cite
|
Sign up to set email alerts
|

Human Poisoning due to Delphinium species in the Himalayan Region of Nepal: A Case Report

Abstract: The Delphinium species herb, common name ‘Nirmasi’ in Nepal, is one of the community level flower herbs used as medicinal ingredients in various clinical problems in Manang District and other Himalayan parts of Nepal. Roots of the plants from the genus Delphinium have been used for a long time for headache, epilepsy, mania, paralysis, rheumatism, toothache, and various types of pain. However, many species of Delphinium are poisonous and look quite similar in morphology to the beneficial ones. As a result, acci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…4 The mechanism of toxicity of this class of alkaloids is neuromuscular paralysis; they compete as post-synaptic inhibitors of the neurotransmitter acetylcholine, specifically, acting at the α 1 nicotinic sites in the mus-cle and brain, causing muscular fatigue, depressed respiration and other curare-like symptoms. 5,6 Our patient presented with complaints of dizziness with syncopal attack secondary to malignant ventricular arrhythmias and hypotension which could be the effect of such alkaloids competitively inhibiting the acetycholine at preganglionic sympathetic synapse blocking the sympathetic outflow to the heart. There has been no specific antidote noted for Delphinium poisoning in humans.…”
Section: Discussionmentioning
confidence: 93%
“…4 The mechanism of toxicity of this class of alkaloids is neuromuscular paralysis; they compete as post-synaptic inhibitors of the neurotransmitter acetylcholine, specifically, acting at the α 1 nicotinic sites in the mus-cle and brain, causing muscular fatigue, depressed respiration and other curare-like symptoms. 5,6 Our patient presented with complaints of dizziness with syncopal attack secondary to malignant ventricular arrhythmias and hypotension which could be the effect of such alkaloids competitively inhibiting the acetycholine at preganglionic sympathetic synapse blocking the sympathetic outflow to the heart. There has been no specific antidote noted for Delphinium poisoning in humans.…”
Section: Discussionmentioning
confidence: 93%
“…Most of the wild flora of Nepal is rich in medicinal properties out of which Delphinium brunonianum has been popularly used for the treatment of many ailments like fever, headache, abdominal pain, jaundice, cough, toxin removal, and skin rashes. However, some species of Delphinium are toxic depending on the chemical constituents of the plant 2 . Tomassoni et al 7 reported the cardiotoxic nature upon consumption of Delphinium manifested as VT. Another study conducted in the Manang district of Nepal reported a case of hypotension and sinus bradycardia after ingestion of Delphinium species 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, some species of Delphinium are toxic depending on the chemical constituents of the plant 2 . Tomassoni et al 7 reported the cardiotoxic nature upon consumption of Delphinium manifested as VT. Another study conducted in the Manang district of Nepal reported a case of hypotension and sinus bradycardia after ingestion of Delphinium species 2 . The index case had accidental poisoning upon consumption of Delphinium manifesting from gastric upset to a severe form of cardiotoxicity that is ventricular storm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations